2021
DOI: 10.1155/2021/3021224
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Regulation, Outward Foreign Direct Investment, and Low-Carbon Innovation: An Empirical Study Based on Provincial Spatial Panel Data in China

Abstract: The low-carbon transformation has turned out to be a challenging task faced by government agencies, enterprises, and society because of the global warming. Endorsing the expansion of the low-carbon revolution is considered as an essential measure for low-carbon alteration and advancement. Therefore, articulating realistic environmental control strategies intended to enhance the motivation level of low-carbon innovation, though outward foreign direct investment (OFDI) can produce direct and indirect influences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 72 publications
(79 reference statements)
0
10
0
Order By: Relevance
“…For this study, the regional industry development was seen as playing a crucial role in bolstering the economic condition, and ultimately promoting inclusive affluence. Building on previous research conducted by Yang [ 32 , 35 ], the panel Attribution-Value Model was cautiously constructed in accordance with the research hypothesis as follows: …”
Section: Methodsmentioning
confidence: 99%
“…For this study, the regional industry development was seen as playing a crucial role in bolstering the economic condition, and ultimately promoting inclusive affluence. Building on previous research conducted by Yang [ 32 , 35 ], the panel Attribution-Value Model was cautiously constructed in accordance with the research hypothesis as follows: …”
Section: Methodsmentioning
confidence: 99%
“…Studies have found that the firms' incentive to emit intensifies as the level of environmental regulation increases, leading to a relaxation of investment in technology development and innovation (Blackman and Kildegaard, 2010), which may even lead to an increase in regional environmental pollution over a certain period of time (Xu, 2016). For example, one study found that public resource-based and market-incentive-based environmental regulations are not conducive to GTFP growth in the short term (Wu et al, 2020), and may also hinder GTFP growth to some extent (Fang and Liu, 2020). In addition, long-term public pressure and media overexposure can put companies in difficult situations regarding their business (Ye, 2021).…”
Section: Study Areamentioning
confidence: 99%
“…At the same time, China’s pilot carbon trading system will gradually increase the positive effect on LTP over time (Liu and Sun 2021 ). In addition, environmental regulation can promote the LTP level to a certain extent (Yang et al 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%